Implementation of a human papillomavirus screen-and-treat model in Mwanza, Tanzania: training local healthcare workers for sustainable impact. Issue 3 (22nd March 2018) - Bernstein, Megan; Hari, Anjali; Aggarwal, Sahil; Lee, Debora; Farfel, Allison; Patel, Priya; Raman, Kaavya; Raja, Shella; Fenning, Reece; Lieber, Mark; Minteer, William; Denny, Sean; et al.
Abstract: Background: The purpose of this study is to evaluate the development of a 1-wk screening campaign and efforts towards the implementation of a sustainable system that addresses cervical cancer in Mwanza, Tanzania with a screen-and-treat model utilizing visual inspection of the cervix with acetic acid (VIA) and cryotherapy. Methods: In partnership with CureCervicalCancer (CCC), a non-profit organization based in Los Angeles, CA, USA, 11 medical students at the University of California, Irvine School of Medicine established a model for sustainable human papillomavirus screening practices in Mwanza, Tanzania. This study both quantitatively and qualitatively assesses the successes and limitations of the program model. Results: During the 5-day training, a total of 614 women attended the screenings and 556 women were screened with VIA, of whom 10.6% (n=59) were VIA positive and 89.4% (n=499) were VIA negative. Of those who were VIA positive, 83.1% (n=49) received cryotherapy while 16.9% (n=10) did not due to suspicion of advanced cancer (n=7), refusal to receive cryotherapy (n=2) or pregnancy (n=1). Conclusions: The screen-and-treat model for the identification and treatment of precancerous cervical lesions is an effective public health intervention with the potential to impact women by providing the tools and education needed by local healthcare professionals. However, limitations common to resource-poor settings, such as continuity of funding, loss to follow-up and transportation costs, remain barriers to sustainability.